Advancing European internal and external digital sovereignty: The Brussels effect and the EU-US Trade and Technology Council - Annegret Bendiek; Isabella Stürzer (Stiftung Wissenschaft und Politik (SWP), 2022)
Given the strong economic interdependencies between the United States (US) and Europe as well as the shared commitment to safeguard civil liberties online and combat disinformation and unfair market practices, European Union (EU) cooperation with the US on digital markets is crucial. Thus, the EU-initiated transatlantic Trade and Technology Council (TTC) was established to navigate European and American understandings of 'digital sovereignty' and the resulting market regulations. The first TTC meeting took place in September 2021 and demonstrated both a shared commitment to building an alliance on 'democratic technology' and diverging ideas on how to best regulate the digital market and its biggest players. As the COVID-19 pandemic has revealed vulnerabilities of international supply chains and accelerated digitalisation, European policymakers are well-advised to continue pursuing their digital foreign policy strategy of advancing digital sovereignty by leveraging the 'Brussels effect', which also fosters the further integration of EU digital policy and contributes to the deepening of the transatlantic digital market.
Keywords: 320